Juridical Analysis on the Position of the National Land Agency of North Morowali Regency in Certificate Issuance of Cultivation Rights Title (Study of PT ANA in East Petasia District) - Megawati Ambo Asa; Irmawaty; Andi Purnawati (Program Pascasarjana Universitas Muhammadiyah Palu, 2022)
This study aims to determine and analyze the implementation of the authority of the National Land Agency of North Morowali Regency in Granting Cultivation Rights Titles to PT. ANA in East Petasia District and to identify and analyze the inhibiting factors for PT ANA in East Petasia District in Cultivation Rights Title Management. This type of research is empirical research, namely the type of research that is oriented towards collecting data in the field. In terms of its nature, this research is a qualitative descriptive research. Qualitative descriptive research is the researcher analyzes and describes the research objectively and in detail to get accurate results. The results of the study found that the implementation of the authority to issue Cultivation Rights Titles was seen from the area of ​​​​the plantation to be managed, the land area of ​​which was not more than 2,000,000 M2 or 200 Ha who was authorized to issue HGU was the Head of the BPN Regional Office, then if the area of ​​land being managed was more of 2,000,000 M2, it becomes the authority of the Head of BPN RI. PT.ANA's inhibiting factors in managing HGU in the East Petasia sub-district include land acquisition/land acquisition not yet completed, land acquisition outside the location permit and/or outside the time limit for the location permit, unclear government administrative boundaries, overlapping permits and land requested. enter the forest area. Research Suggestion is that the district government should provide socialization related to the authority of the National Land Agency in the issuance of Cultivation Rights Titles and supervise oil palm plantation companies operating in North Morowali Regency as well as take action against companies that do not have Cultivation Rights Titles and preferably to PT. ANA to immediately complete the issuance of the Cultivation Rights Title in running the company even though it already has a location permit and a Plantation Business Permit from the Regent.